(untitled) (Modern education and development, 2025)
This article analyzes the benefits of knowledge bases and their management methods. The article examines the main benefits of knowledge bases, including the ability to systematically store knowledge, support innovation, make effective decisions, and develop skills. The article emphasizes the important role of knowledge management in increasing the competitiveness of organizations and improving their operational efficiency.